Pharmacokinetics and penetration into synovial fluid of systemical and electroporation administered sinomenine to rabbits. (7th November 2014) - Yan, Huan; Yan, Miao; Li, Huan‐De; Jiang, Pei; Deng, Yang; Cai, Hua‐lin
Abstract Sinomenine is an anti‐rheumatoid arthritis (RA) drug derived from the Sinomenium acutum. The major site of RA treatment is within the synovial compartment. However, the pharmacokinetic and penetration into synovial fluid (SF) of sinomenine have not been reported. In our study, the pharmacokinetics and penetration into SF of systemic and electroporation administered sinomenine were investigated by microdialysis incorporated with HPLC‐MS/MS. Sinomenine went into plasma and SF more rapidly with higher peak concentration (Cmax) by intramuscular injection compared with oral administration. The area under the concentration–time graph (AUC0–∞) of intramuscularly injected sinomenine was 1, 403, 294.75 ± 125, 534.567 ng min/mL in plasma and 456, 116.37 ± 62, 648.36 ng min/mL in SF, which were equivalent with those for an oral dose. These results indicated that equal amounts of sinomenine could penetrate into SF by the two administration routes, and the permeation ratios were approximately 1:3. The AUC0–∞ and Cmax were lower with electroporation compared with systemic administration, but the CSF/CPlasma (concentration of sinomenine in SF vs that of plasma) at 90, 120, 150, 180, 240 and 480 min by electroporation was 3‐ to 10‐fold higher relative to systemic administration. This illustrated that sinomenine can be targeted into joints by electroporation, and electroporation is a potential technique for sinomenine's transdermal delivery. Copyright © 2014 John Wiley & Sons, Ltd.